Usefulness of local buffer data for WWW objects prefetching. (26th September 2008) - Sieminski, Andrzej
The sole aim of the prefetching of WWW objects is to shorten the Time To Display (TTD) of web pages. The paper indicates that user oriented prefetching has a great potential. The paper discuses the pros and cons of exploiting the browser buffer as a data-mining source. Despite its limitations, the buffer is a valuable source of data about the user navigational habits and the properties of fragment of the WWW that he or she visits. Such data is difficult to obtain or even not available from other sources. The extracted data could be used for the design of user oriented prefetching.